Quality Control Optimization in Improving Production Management at PT. WimanSejahtera Makassar: Quality Control in Improving Production - Muhammad Luthfi Siraj; Syarifuddin Syarifuddin (Public Resource Innovation Management and Excellence, 2025)
This study aims to analyze and optimize the quality control system in improving the effectiveness of production management at PT Wiman Sejahtera Makassar. The focus of the study is how the application of the concepts of Total Productive Maintenance (TPM), Lean Manufacturing, Total Quality Management (TQM), and Six Sigma can improve equipment availability, production performance, and product quality in a sustainable manner, thereby supporting the company's competitiveness and customer satisfaction. The research method used is descriptive quantitative research with a case study approach, supplemented by performance analysis based on Overall Equipment Effectiveness (OEE) indicators, namely availability, performance, and quality. Data was obtained through direct observation, interviews with production staff, and documentation related to machine maintenance records, productivity, and product defect rates. The results of the study show that equipment availability reached 85%, production performance was 90% of the ideal speed, and product quality was 95%, indicating that there is still potential for improvement in operational efficiency and quality control. Optimizing quality control through the integration of TPM, Lean Manufacturing, TQM, and Six Sigma has been proven to reduce downtime, streamline production flow, improve employee skills and motivation, and reduce product defect rates. Thus, the implementation of a structured and sustainable quality control system can create more adaptive, reliable, and customer-oriented production management, while strengthening the company's competitiveness in the industrial market.